On the evolution of Boolean networks for computation: a guide RNA mechanism. Issue 2 (3rd March 2016) - Bull, Larry
Abstract : There is a growing body of work within computational intelligence which explores the use of representations inspired by the genetic regulatory networks of biological cells. This paper uses a recently presented abstract, tunable model of such networks to investigate how their design through simulated evolution is affected through the ability to dynamically rewire connectivity. The contextual editing of transcribed RNA by other molecules such that the form of the final product differs from that specified in the corresponding DNA sequence is ubiquitous. It is here shown that a guide RNA-inspired editing mechanism can be selected for under various scenarios.